Waste Brick Dust as Potential Sorbent of Lead and Cesium from Contaminated Water - Doušová, Barbora; Koloušek, David; Lhotka, Miloslav; Keppert, Martin; Urbanová, Martina; Kobera, Libor; Brus, Jiří (Materials (Basel, Switzerland), 2019)
Adsorption properties of waste brick dust (WBD) were studied by the removing of PbII and CsI from an aqueous system. For adsorption experiments, 0.1 M and 0.5 M aqueous solutions of Cs+ and Pb2+ and two WBD (Libochovice-LB, and Tyn nad Vltavou-TN) in the fraction below 125 µm were used. The structural and surface properties of WBD were characterized by X-ray diffraction (XRD) in combination with solid-state nuclear magnetic resonance (NMR), supplemented by scanning electron microscopy (SEM), specific surface area (SBET), total pore volume and zero point of charge (pHZPC). LB was a more amorphous material showing a better adsorption condition than that of TN. The adsorption process indicated better results for Pb2+, due to the inner-sphere surface complexation in all Pb2+ systems, supported by the formation of insoluble Pb(OH)2 precipitation on the sorbent surface. A weak adsorption of Cs+ on WBD corresponded to the non-Langmuir adsorption run followed by the outer-sphere surface complexation. The leachability of Pb2+ from saturated WBDs varied from 0.001% to 0.3%, while in the case of Cs+, 4% to 12% of the initial amount was leached. Both LB and TN met the standards for PbII adsorption, yet completely failed for any CsI removal from water systems.
Keywords: lead; surface complexation; waste brick dust; precipitation; cesium; solid-state NMR spectroscopy; adsorption